Micropropagation of Bioencapsulation and Ultrastructural Features of Sainfoin (Onobrychis viciifolia) Grown In Vivo and In Vitro - Sadegh Mohajer; Rosna Mat Taha; Minoo Mohajer; Arash Khorasani Esmaeili (The Scientific World Journal)
To explore the potential of in vitro rapid regeneration, three varieties (Golpaygan-181, Orumieh-1763, and Gorgan-1601) of sainfoin (Onobrychis viciifolia Scop. syn. Onobrychis sativa L.) were evaluated. For the first time, an encapsulation protocol was established from somatic embryogenic callus in torpedo and cotyledonary stages to create artificial seeds. Callus derived from different concentrations of Kinetin (0–2.0 mg L−1) and Indole-3-acetic acid (0–2.0 mg L−1) was coated with sodium alginate and subsequently cultured either in Murashige and Skoog (MS) medium or in soil substrate. Adventitious shoots from synthetic beads developed into rooting in full and half strength MS medium supplemented with various concentrations of auxin and cytokinin. Prolonged water conservation of black and red soils (1 : 1) had the highest rate of survival plantlets in the acclimatization process. Diverse resistance techniques in Onobrychis viciifolia were evaluated when the plants were subjected to water deficiency. Higher frequency of epicuticular waxes was observed in in vivo leaves compared to in vitro leaves. Jagged trichomes nonsecreting glands covered by spines were only observed in the lower leaf side. Ultimately, stomata indices were 0.127 (abaxial), 0.188 (adaxial) in in vivo and 0.121 (abaxial), 0.201 (adaxial) in in vitro leaves.